A valoração da prova testemunhal : um estudo comparativo entre o Direito Brasileiro e o Direito Federal dos Estados Unidos da América - Ferraro, Felipe Waquil (2016)
Television is a specific form of cultural expression of a particular people. In this sense, the influence of the television and American movies in the rest of the world is overwhelming, with a reference to the public and society in general. This influence can also be seen in the legal world. American cinemas are rich in films with courts in which lawyers masterfully dominate the causes, the evidence, the witnesses and the jury. It has also, throughout the North American legal culture shown on tv series, that are broadcast in several countries. Thus, it is huge the influence of television on the culture of a society, which has often clients leaving of an audience really disappointed because the lawyer didn’t won the case, not constrains the other party to give up the case or did not show all his oratory to the judge. Finally, at the end of an ordinary audience of Civil Law, still hears "It's that all, counselor?" In this regard, the appeal by the shock, characteristic of the Common Law system, deserves a detailed analysis. This analysis will be done from the testimonial evidence. Thus, this dissertation aims to verify the contrast between Brazilian Law (Civil Law) and the US Law (Common Law), as well, the elements which approach and contrast them, especially about the testimonial evidence, specifically in its rules exclusion and valuation systems. Therefore, we’ll see, the systematic structure of the Law of the United States, starting from the Constitution (Bill of Rights), passing by federal rules (Federal Rules of Civil Procedure and Federal Rules of Evidence) to the traditional issues such as exclusion rules and the civil jury. Then, we will analyze the problem of studying distinct systems as Civil Law and Common Law, knowing that it allows us a wide view of the elements that distinguish them. In this regard, we have the investigation of orality in the US Common Law system, in front of the jury figure and the form of inquiry and influence witnesses. Therefore, we’ll see the exclusion rules and the assessment of the evidence based on the US legal system, as also, see the absolute need for a proper understanding of evidentiary standards. At the end, you can not only see the influence of American law, but also understand their particularities, pros and cons, across the Brazilian law.